The process of confrontation with disability in patients with spinal cord injury - Ahmadzadeh, Gholamhossein (Medknow Publications Pvt Ltd, 2010)
BACKGROUND: Spinal injury can establish severe psychological outcomes for the patient and his/her family which requires high adjustment. Health system staff would be able to play their roles well in caring these patients provided with knowing what steps spinal injured people should pass to handle their disability and also what assistance they need in what stages from what sources. This study aimed to explain the process of confrontation with disability in spinal cord injured patients. METHODS: This was a qualitative study with grounded theory approach which was performed in Strauss and Corbin proposed method on twenty people with spinal cord injury who had past at least three months from their spinal injury. Sampling was done in purposive and theoretical method, and analysis of the results was also performed during constant comparative process. RESULTS: Central concept in the data was support which was associated with other concepts and affected them. The patients, with the help of internal and external support could overcome their main problem that was disability feeling and dependency on others and find a new definition for the self, and ultimately achieve the sense of independence and autonomy. CONCLUSIONS: Knowing the process of confrontation with disability along with better understanding of spinal cord injured people would help health system staff to actualize and support their potentials much better through strengthening internal resources and providing appropriate supportive services of each individual.